Economy of fuel-energy resources on rail-freight traffic improving the exploitations characteristics of fuel consumption of diesels - Lebedevas, Sergejus (Transport, 2002)
The improvement of the exploitation features of diesel power units oflocomotives is one of the most important aspects solving the problems of saving fuel energy resources (FER) in the rail-freight traffic system. It covers in full the following: the increase of specific fuel economy factors, the optimizaition of load cycles used park of locomotive diesels and the introduction of informational technologies in operative checking systems and normalizing FER. On the base of modem accounting methods of mathematical simulation on PC the expected reserve of reducing the expenses on the fuel is evaluated for the most frequent type of diesels in Lithuania such us 14Д40Y2 in diesel locomotive M62(2M62). The regulation of units of systems of fuel injection and aeroprovision for the seasonal periods “winter-summer” and the optimum of their loading accordingly allows to reach fuel economy 1,5–3,0% and 6,5–8,0%. Rational base of algorithm for automatic checking systems and normalizing FER on enterprises of rail-freight traffic is a method of small incrementations, in combination with the use of databases of the technical characteristics of power units park. Standard draft model similar to accounting-information complex “Profil” is designed by specialists of Klaipėda university.Article in Lithuanian.Energinių išteklių išsaugojimas geležinkelių transporte, tobulinant šilumvežių dyzelių eksploatacines kuro suvartojimo charakteristikasSantrauka. Nagrinėjamas energinių išteklių išsaugojimo geležinkelių transporte kompleksinis sprendimas optimizuojant šilumvežių dyzelių reguliavimo ir apkrovos režimu įgyvendinant sukurtą informacinės technologijos, kontrolės ir normavimo specializuotą ESM programinę įrangą valdymo ir techninio aptarnavimo infrastruktūrose. Pagrįstas dyzelino ekonomijos efektas labiausiai eksploatuojamam Lietuvoje M62 (2M62) lokomotyvų parkui, siekiantis nuo 6 % iki 8 %.Raktažodžiai: energinių išteklių išsaugojimas, šilumvežio dyzelis, ESM normavimo ir kontrolės sistemos.First Published Online: 19 Oct 2011